Hematopoietic Stem and Progenitor Cells Can Be Enriched by Implanting Biomaterial into Spatium Intermusculare. (28th January 2015) - Tong, Jia-Bei; Wu, Xiao-Yun; Jia, Ge-Liuchang; Zhao, Kui-Jun; Wang, Shi-Li; Ma, Zhi-Jie
Abstract : Hematopoietic stem and progenitor cells (HSPCs) have been used successfully to treat patients with cancer and disorders of the blood and immune systems. In this study, we tried to enrich HSPCs by implanting biomaterials into the spatium intermusculare of mice hind limbs. Gelatine sponges were implanted into the spatium intermusculare of mice and then retrieved after 12 days. The presence of HSPCs in the migrating cells (MCs) was detected by phenotypically probing with CD34 + Sca-1 + and functionally confirming the presence of using colony-forming cell assay and assessing the long-term reconstitution ability. The frequency of CD34 +, Sca-1 +, and CD34 + Sca-1 + cells and colony formation unit in the MCs was much higher than that in the bone marrow (BM). Moreover, transplanted MCs were able to home to BM, muscle, and spleen, which induced an efficient long-term hematopoietic reconstitution in vivo. In addition, HSPCs within the MCs originated from the BM. Furthermore, the administration of G-CSF greatly reduced the time of implantation, and increased the number of MCs and frequency of HSPCs in the MCs. These data provide compelling evidence that HSPCs can be enriched by implanting biomaterial into spatium intermusculare. Implantation of biomaterial may be seen as the first step to a proof of their applicability to clinical practice in enriching HSPCs.